(untitled) - Underwood, Deborah; Hunt, Meg (San Francisco, 2019)
In this version of Sleeping Beauty, told in verse, the Princess is threatened with a curse which will start with a paper cut; devastated that all her books have been taken away, she sets out with her dog, Prince, to find the fairy who cast the curse and make her reverse it.
Keywords: Fiction; Books and reading; Fiction; Fairies; Fiction; Juvenile fiction; Literacy; Blessing and cursing; Books and reading; Juvenile fiction; Fairies; Juvenile fiction; Blessing and cursing; Adaptations; Sleeping Beauty (Tale); Juvenile fiction; Stories in rhyme; Fairy tales